Techno-economic performance of mechanised fishing in Karwar, Karnataka - Aswathy, N.; Narayankumar, R.; Harshan, N. K.; Ulvekar, C. (Indian Journal of Fisheries, 2017)
The techno-economic and financial performance of mechanised purse seiners and trawlers operating in Karwar Fishing Harbour was compared using various indicators. The average diesel consumption per trip was 179 l for purse seiners and 79 l for trawlers. The average operating cost and gross revenue per trip were `21,818 and `44,383 respectively for purse seiners and `4,803 and `6,571 respectively for trawlers. Oilsardines and mackerels contributed more than 85% of the catch of purse seiners whereas shrimps and flatfishes contributed nearly 50% of the catch of trawlers. Capital productivity was higher (operating ratio - 0.49) for purse seiners than trawlers (operating ratio - 0.73). The economic and financial performance indicators like net benefit-earnings ratio (0.43), benefit-cost (BC) ratio (1.75) and internal rate of return, IRR (117%) were higher for purse seiners which suggested that the investment on purse seiners is a more viable undertaking when compared to trawlers in the location.